1997
DOI: 10.1359/jbmr.1997.12.5.769
|View full text |Cite
|
Sign up to set email alerts
|

Early Responses to Dynamic Strain Change and Prostaglandins in Bone-Derived Cells in Culture

Abstract: Mechanical loading of bone explants stimulates prostaglandin E 2 (PGE 2 ) and prostacyclin (PGI 2 ) release and increases glucose 6-phosphate dehydrogenase (G6PD) activity. This response is blocked by indomethacin and imitated by exogenous PGs. In the experiments reported here, primary cultures of rat long bone-derived osteoblast-like cells were exposed to a dynamic strain and exogenous PGs in the culture dish. Strain (3400 , 600 cycles, 1 Hz) caused an immediate release of PGI 2 into the culture medium but ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 53 publications
1
86
0
Order By: Relevance
“…ER␣-null mutant mice (ER␣ Ϫ/Ϫ ) (31) were a gift from Professor Pierre Chambon. Cell Culture-Primary osteoblast-like cells were prepared from the long bones of 17-week-old female ER␣ Ϫ/Ϫ mice and their WT littermates as previously described (32).…”
Section: Methodsmentioning
confidence: 99%
“…ER␣-null mutant mice (ER␣ Ϫ/Ϫ ) (31) were a gift from Professor Pierre Chambon. Cell Culture-Primary osteoblast-like cells were prepared from the long bones of 17-week-old female ER␣ Ϫ/Ϫ mice and their WT littermates as previously described (32).…”
Section: Methodsmentioning
confidence: 99%
“…The mechanical strain stimulus comprised uniaxial dynamic (1 Hz) mechanical strain with a peak magnitude of 3800 ⑀. This was applied for 10 min using a specifically designed loading jig by four-point bending of plastic strips (Nunc) onto which the cells had been seeded as previously described (25,(27)(28)(29). This essentially imparts tensile strain in a controlled manner by bending of the cell culture-treated plastic strips onto which cells have been previously seeded.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that mechanical stress plays an important role in the progression of OPLL (Kitajima et al, 2001). Furthermore, mechanical stress produces PGI 2 in osteoblasts (Rawlinson et al, 1993;Zaman et al, 1997). To investigate the relationship between PGI 2 signaling and mechanical stress, we performed RT-PCR with primers for PGI 2 synthase.…”
Section: Differential Display Rt-pcrmentioning
confidence: 99%